Chapter 10 Between appropriation and appropriateness : Instrumentalizing dark heritage in populism and memory? (2020)
This chapter takes an interdisciplinary approach to the subject of memorialization and commemoration, protest and populism in relation to the performative enacting and official presentation of difficult history. It analyzes the various actors instrumentalizing the same dark heritage in different ways, by different means, and for different purposes, to draw conclusions about processes of coming to terms with the past ( Vergangenheitsbewältigung ) in relation to the contemporary context of populism and migration.